Prophet und König im Nordreich Israel : Studien zur sogenannten vorklassischen Prophetie im Nordreich Israel anhand der Samuel-, Elija- und Elischa-Überlieferungen - Lehnart, Bernhard. (Vetus Testamentum, Supplements, 2003)
The present book deals with the so-called "pre-classical" prophecy in the Northern Kingdom of Israel. It becomes evident that the introduction of kingship in the early period of prophecy marks the beginning of a consideration of social situations. The prophet is placed over the king and stylized as the actual saviour figure. This development is examined along with the extensive prophetic traditions of Samuel, Elijah and Elisha. The texts are first analyzed from a diachronic standpoint to determine pre-deuteronomistic text components. These texts are then linked to their historical context and examined with respect to their medium and historicity. This book throws new light on the social and socio-structural importance of prophecy in this early period.